Simulink Model of Vector Controlled Linear Induction Motor with End Effect for Electromagnetic Launcher System - Korkmaz, F.; Topaloglu, I.; Gurbuz, R. (Elektronika ir Elektrotechnika, 2014)
Today, linear induction motors spread out in the field of transportation and many industrial fields such as railway and electromagnetic launcher systems. Especially, high efficiency control and fast dynamic response are demanded for electromagnetic launcher systems and it’s well known that direct torque control scheme provides fast dynamic response for rotary induction motors. This paper describes Simulink model of direct thrust controlled linear induction motor with end effect for electromagnetic launcher system and presents a simple and effective scheme for direct thrust control of a linear induction motor. The Simulink model of single sided linear induction motor with end effect developed to realize the direct thrust control. To show the effectiveness of the improved system, simulation results are presented using commercially available software package Matlab/Simulink. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6161